The Organization of Workmen's Compensation Insurance - Downey, E. H. (Journal of Political Economy, 1916)
American experience with compensation insurance, while not of long duration, is extremely varied in character. We have monopolistic and semi-monopolistic state funds, competing state funds, stock-insurance ompanies, mutual associations, interinsurance exchanges, and the hybrid stock-mutual companies. It is even by no means uncommon to find all these types of insurance carriers (except the first) coexisting in the same state. Not content with this great variety of options, nearly all American jurisdictions provide as well for what, by a naive paradox, is styled self-assurance-which, ofcourse, is not a form of insurance at all, but the negation of it. Indeed, the only important European experiment not hitherto tried upon this continent is the compulsory mutual association of the well-known German pattern. All this diversity springs neither from chance nor from constructive statesmanship; it reflects, rather, a very lively conflict of views and interests. The best type of organization for workaccident insurance has yet to approve itself to American public opinion. In the meanwhile, a majority of our legislatures have left the problem to work out its own solution through trial and error. The present is, therefore, an opportune moment o examine American and foreign experience in the light of those fundamental principles of public policy which should govern any branch of social insurance. Workmen's compensation insurance aims both to guarantee the payment of accident benefits and to distribute the' cost thereof over the community at large. Both these objects are essentially involved in the public ends for which workmen's compensation laws are enacted, and neither can be attained without effective insurance. Any system of work-accident indemnity which is at all adequate for its purpose must provide life-pensions for permanent disabilities and pensions for long terms of years to the